Additions of Protozoan to Pantanos de Villa fauna, Lima, Peru - Guillén, Gisella (2003)
Monthly surveys between October 1999 to August 2000 were carried out in nine stations from ponds of the Pantanos de Villa, Chorrillos, Lima. It was determined 128 species of protozoa, distributed in 101 genus, 69 families and 28 orders. A total of 73 species were new report in Pantanos de Villa. At the present time a total of 171 species of protozoa had been reported. The Ciliate was more diverse group with 61,72% of species, following for Mastigophora (21,9%) and Sarcodina (16,4%). The highest abundance was Mastigophora (75%), following Ciliate (19,5%) and Sarcodina (4,5%).